(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The purpose of this study was to recognize the degree of physical education supervisors practice for the participatory and supervisory behavior and its connection to improve the performance of teachers from the perspective of physical education teachers. The researcher used the descriptive approach because it’s appropriate for the nature and the objectives of the study. The study sample consists (241) of physical education teachers in Irbid governorate, and after reviewing the conceptual framework and the previous studies such as: Al- Hajri and Harahsheh studies (2016), Al- Dajani study (2013), Al- Balawi study (2008), Al- Afandi study (2011), Hamad study (2014). The researcher built the study tool and conducted its credibility and statistical stability. Eventually, the study consisted of (7) axes and they are: (professional growth, planning for better performance, evaluation, curricular analysis, behaviors, skills and academic performance). The findings of this study were that the degree of the supervisors’ practice for the participatory and supervisory behavior was moderate, whereas the level of improving teachers’ performance was high. The connection between the degree of practice the supervisory behavior and improve teachers’ performance was positive. The researcher recommend conducting training courses, workshops, and training programs for physical education supervisors about the concept of participatory supervision and the way of activating and applying this concept in the field of physical education to improve the supervisors’ practice of the participatory and supervisory behavior.